(untitled) (Research, Society and Development, 2025)
Objective: To investigate and profile the antimicrobials prescribed at the Emergency Care Unit of Icoaraci, Belém, Pará. Methodology: Cross-sectional, exploratory, retrospective study covering the years 2021, 2022, and 2023, using medical records to establish the frequency and pattern of antimicrobial use. The data were described and analyzed using Microsoft Excel 2016. Results: A predominance of six pharmacological classes was observed over the three years evaluated: cephalosporins representing 52.60% of the total, macrolides and lincosamides both representing approximately 11.86%, nitroimidazoles with 10.65%, fluoroquinolones with 5.64%, and penicillins with 4.18%. Ceftriaxone (Cephalosporin) was the most prescribed antimicrobial among the 4,715 prescriptions collected, representing 46.70%, and was primarily associated with the diagnostic hypothesis of pneumonia (29.70%). Conclusion: The findings highlight the need for an in-depth analysis of the appropriateness of the use of broad-spectrum antimicrobials such as ceftriaxone, especially in urgent and emergency care, where empirical therapy is frequent. The correlation between the prescribed antimicrobial and the diagnostic hypothesis reflects the expected epidemiological profile for an emergency unit.